(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article highlights the role and importance of guiding activities in the development of tourism in the Republic of Uzbekistan. It analyzes the tasks of guides in conveying national culture, historical heritage and traditions to tourists in a correct and understandable manner. It also considers the contribution of the guiding service to the formation of the country’s tourism image, increasing the flow of foreign and domestic tourists, and the economic development of the tourism sector. The article also pays special attention to the issues of the system of training guides, their professional qualifications and adaptation to the requirements of modern tourism.